Evaluation of Solvent Effect (Methanol: Water Mixture) on the Phenolic Content and Antioxidant Activities of Stachys turcomanica Trautv - Khashayar Namvar, Ameneh Mohammadi, Esmail Ataei Salehi, Peyman Feyzi (Tabriz University of Medical Sciences, 2017)
Background: The genus of Stachys with 300 species belongs to Lamiaceae family and this genus has 34 species in Iran. Stachys turcomanica Trautv is native to Iran and it used for treatment of infectious, rheumatic and inflammatory diseases in traditional medicine. The effect of solvent (methanol in water: 0, 20, 50, 80 and 100 %) on the extraction of antioxidant compounds from S. turcomanica were investigated using various in vitro assays. Methods: The antioxidant activities of extracts were studied via three methods: FRAP (ferric reducing antioxidant power), DPPH (2, 2-diphenyl-1-picrylhydrazyl) and beta-carotene linoleic acid bleaching. Results: The results of present work revealed that the solvent combinations have effects on the extraction of phenolic compounds and antioxidant properties. The relative methanol/water ratio of 80:20 v/v was effective solvent in the extracting of phenolic compounds. Also, there was a good correlation between antioxidant activity and total phenolic content S. turcomanica extracts. Conclusion: The results demonstrated methanol/water (80:20) ratio was the best solvent to release of many secondary metabolites from S. turcomanica for future studies, which could provide natural sources of antioxidant compounds.